Human induced pluripotent stem cells are a novel source of neural progenitor cells (iNPCs) that migrate and integrate in the rodent spinal cord. Issue 12 (12th April 2014) - Sareen, Dhruv; Gowing, Geneviève; Sahabian, Anais; Staggenborg, Kevin; Paradis, Renée; Avalos, Pablo; Latter, Jessica; Ornelas, Loren; Garcia, Leslie; Svendsen, Clive N.
ABSTRACT Transplantation of human neural progenitor cells (NPCs) into the brain or spinal cord to replace lost cells, modulate the injury environment, or create a permissive milieu to protect and regenerate host neurons is a promising therapeutic strategy for neurological diseases. Deriving NPCs from human fetal tissue is feasible, although problematic issues include limited sources and ethical concerns. Here we describe a new and abundant source of NPCs derived from human induced pluripotent stem cells (iPSCs). A novel chopping technique was used to transform adherent iPSCs into free‐floating spheres that were easy to maintain and were expandable (EZ spheres) (Ebert et al. [2013] Stem Cell Res 10:417–427). These EZ spheres could be differentiated towards NPC spheres with a spinal cord phenotype using a combination of all‐trans retinoic acid (RA) and epidermal growth factor (EGF) and fibroblast growth factor‐2 (FGF‐2) mitogens. Suspension cultures of NPCs derived from human iPSCs or fetal tissue have similar characteristics, although they were not similar when grown as adherent cells. In addition, iPSC‐derived NPCs (iNPCs) survived grafting into the spinal cord of athymic nude rats with no signs of overgrowth and with a very similar profile to human fetal‐derived NPCs (fNPCs). These results suggest that human iNPCs behave like fNPCs and could thus be a valuable alternative for cellular regenerative therapies of neurological diseases. J. Comp. Neurol. 522:2707–2728, 2014. © 2014 Wiley Periodicals, Inc.